Code-switching and Language-mixing among the AFL students of Chennai: Influence of Mother Tongue on the Use of Arabic as the Second Language - K. M. A. AHAMED ZUBAIR (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2025)
Issues surrounding the use of foreign languages and mother tongues (code-switching) in language classrooms have garnered significant research interest. This study explores the factors driving code-switching among students and teachers during various phases of interaction in an Arabic as a Foreign Language (AFL) classroom. The investigation focuses on mother tongue interference and its impact on learning Arabic as a second language at The New College, Chennai, India. Identifying these challenges is essential to address the needs of students striving to master Arabic effectively. Using a quantitative survey method, the study analyses written examination scripts from high-performing, average, and low-performing students. The tests assess grammar, spelling, sentence structure, and punctuation. Data were analyzed using descriptive statistics, with tools like Microsoft Excel and SPSS used to calculate the percentage and frequency of language errors. The findings revealed four major error types: grammar (49%), spelling (24.4%), sentence structure (22.2%), and punctuation (4.4%). These results underline how interference from the Tamil mother tongue influences students' Arabic learning. The study highlights the need for tailored instructional strategies to address language errors stemming from native-language interference. By understanding the specific areas where students struggle, educators can better facilitate their language acquisition. The research underscores the importance of considering the linguistic background of learners in second language instruction and offers recommendations to enhance teaching methodologies, ultimately improving students’ proficiency in Arabic.